CD40 Engagement on Endothelial Cells Promotes Tissue Factor-dependent Procoagulant Activity - Zhou, Ling; Stordeur, Patrick; Lavareille, Aurore de; Thielemans, Kris; Capel, Paul; Goldman, Michel; Pradier, Olivier (Thrombosis and Haemostasis, 1998)
The CD40 molecule expressed on endothelial cells has been shown to transduce activation signals resulting in upregulation of adhesion molecules. Herein, we studied the impact of CD40 engagement on the induction of tissue factor (TF)-dependent procoagulant activity (PCA) at the surface of human umbilical vein endothelial cells (HUVECs). First, we found that co-incubation of HUVECs with 3T6 fibroblasts transfected with the CD40L gene (3T6-CD40L) resulted in a clear induction of PCA which was not observed with control untransfected fibroblasts. The specificity of this finding was established by inhibition experiments using monoclonal antibodies (mAbs) blocking CD40 or CD40L. PCA induced by CD40 ligation was TF-related as it was not observed in factor VII-deficient plasma and was associated with the accumulation of TF mRNA. To investigate the role of CD40/CD40L interactions in the induction of endothelial cell PCA by lymphocytes, interferon (IFN)-γ-stimulated EC were incubated with T cells in the absence or presence of anti-CD40 or anti-CD40L mAb. The 60-70% inhibition of PCA induced by these mAbs but not their isotype-matched control indicated that the CD40 pathway is involved in the induction of PCA resulting from interactions between activated HUVECs and T cells. We conclude that activation signals elicited by CD40 engagement on endothelial cells result in the induction of TF-dependent PCA. The CD40/CD40L pathway might therefore be involved in the development of prothrombic states during diseases associated with endothelial cell and T cell activation.